An In-depth Analysis of the Contemporary Biological Characteristics of Aedes Mosquitoes in Laboratory Conditions - Abu Bakar, Azlinda; Zainudin, Muhammad Nur Hilmi (Journal of Sustainable Natural Resources, 2024)
Aedes aegypti and Aedes albopictus are recognized vectors of various arboviruses, including dengue, Zika, and chikungunya, contributing significantly to global public health challenges. The investigation aimed to clarify essential aspects of the biological dynamics of both Aedes species under standardized laboratory conditions. This included developmental duration, adult lifespan, gonotrophic cycle, and morphometric parameters across various life stages. Findings revealed that the lifecycle completion of Ae. aegypti and Ae. albopictus in laboratory settings averaged approximately 8.75 days and 10.35 days, respectively, with no statistically significant difference observed between the two species. Intriguingly, a notable difference in longevity was observed between male and female mosquitoes, with females showing significantly longer lifespans (P<0.05). Specifically, male Ae. aegypti demonstrated a mean survival time of 24 days, contrasting with females’ longevity of 33.80 days. Similarly, male Ae. albopictus displayed a mean lifespan of 16.60 days, while females persisted for approximately 21.40 days. Morphometric analyses revealed subtle yet noteworthy differences, with Ae. aegypti exhibiting slightly larger egg dimensions (0.567 mm) compared to Ae. albopictus (0.526 mm). Similarly, pupal cephalothorax measurements revealed a slight difference, with Ae. aegypti measuring 2.021 mm and Ae. albopictus measuring 1.928 mm. In conclusion, these findings provide valuable insights into the intricate biology of Aedes mosquitoes, thereby facilitating the development of targeted strategies for disease control and mitigation. Such endeavors are crucial in the ongoing battle against arboviral diseases and underscore the significance of rigorous scientific inquiry in public health initiatives.